2009
DOI: 10.1007/s10658-009-9539-7
|View full text |Cite
|
Sign up to set email alerts
|

Fitness cost of virulence differs between the AvrLm1 and AvrLm4 loci in Leptosphaeria maculans (phoma stem canker of oilseed rape)

Abstract: ???The original publication is available at www.springerlink.com??? Copyright Springer [Full text of this article is not available in the UHRA]To investigate whether the reported fitness cost of virulence at the AvrLm4 locus in Leptosphaeria maculans is common to other loci, near-isogenic (NI) isolates differing at AvrLm1 locus were produced in vitro. Fitness of virulent (avrLm1) or avirulent (AvrLm1) isolates on Brassica napus without the corresponding R (resistance) gene Rlm1 was investigated in controlled e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(68 citation statements)
references
References 31 publications
(50 reference statements)
1
67
0
Order By: Relevance
“…Zhan and McDonald (2013) observed that fitness cost of mutation of avirulence genes of fungi can affect the effectiveness of recycling the corresponding resistance gene in crops. Fitness costs are associated with mutation of AvrLm1 and AvrLm4 in L. maculans (Huang et al 2010). This is consistent with our observations of much higher frequencies of AvrLm1 in fungal populations in regions in Australia where cultivars with Rlm1 resistance have not been sown, compared to areas where these cultivars have been extensively sown.…”
Section: Recycling Resistance Genes and Pathogen Fitnesssupporting
confidence: 91%
“…Zhan and McDonald (2013) observed that fitness cost of mutation of avirulence genes of fungi can affect the effectiveness of recycling the corresponding resistance gene in crops. Fitness costs are associated with mutation of AvrLm1 and AvrLm4 in L. maculans (Huang et al 2010). This is consistent with our observations of much higher frequencies of AvrLm1 in fungal populations in regions in Australia where cultivars with Rlm1 resistance have not been sown, compared to areas where these cultivars have been extensively sown.…”
Section: Recycling Resistance Genes and Pathogen Fitnesssupporting
confidence: 91%
“…On the one hand, positive and negative fitness costs of effectors were demonstrated in rare field studies involving the fungus Leptosphaeria maculans (Huang et al, 2006, 2010) or the bacterium Xanthomonas oryzae pv oryzae (Vera Cruz et al, 2000). Under controlled conditions, a reduced number of ‘avirulence’ activities had a significant negative impact on fitness as in the case of Phytophthora infestans infecting potato (Montarry et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a number of studies have attempted to measure such costs in either the field or under controlled conditions (e.g., Chin & Wolfe, 1984; Huang et al., 2006, 2010; Barrett, Bell, Dwyer, & Bergelson, 2011; Zhan & McDonald, 2013). However, temporal changes in infectivity patterns in agricultural systems are not always consistent with theoretical expectations.…”
Section: Discussionmentioning
confidence: 99%